Overview of online pharmacy regulations in Saudi Arabia and the Gulf cooperation council countries and their impact on online pharmacy service providers in Saudi Arabia: a qualitative analysis - Alfageh, Basmah H.; Abanmy, Norah O.; Kentab, Basma Y.; Almohammed, Omar A. (Frontiers in Pharmacology, 2024)
Laws and regulations are needed to regulate the growing online pharmacy (OP) services. The main objective of this work was to provide an overview of the laws and regulations for OP services in the Gulf Cooperation Council (GCC) countries. In addition, the perception of how these laws and regulations in Saudi Arabia (SA) affect the online ordering of medications and health-related products from national and international OPs was explored. A secondary data collection through emails and a qualitative descriptive analysis was used to gain insight into the OP regulations in the GCC countries. Then, a qualitative study was carried out with semi-structured interviews to investigate the impact of these regulations on the practice and the market from the OP service providers' perspective. The interviews were carried out with a sample of major OP service providers in SA, to represent the GCC countries. During the interviews, multiple open-ended questions were used to explore opinions about the OP regulations and how these regulations affected the practice. The interviews were then transcribed and thematically analysed. Responses were mainly received from regulators in SA, Bahrain, Oman and United Arab Emirates (UAE). SA and UAE allow for offering of OP services as add-on service for existing community pharmacy, while UAE also allows for standalone OP providers. SA, Bahrain, and Oman allow online ordering of both over-the-counter (OTC) and prescription-only medications (POM) from international OP; a prescription is required for POM and quantities allowed should be no more than three months' supply in case of SA and Oman while this was not specified in case of Bahrain. Invoice of purchase was also required for any POM to be released from customs in SA and Bahrain but not in Oman and UAE. Controlled medications were prohibited to be ordered online in SA, UAE, and Bahrain while it was allowed in Oman if the prescription was issued within 6-month, and the quantity dispensed was for one month only. The existing regulations for online ordering of medications are somewhat comparable between the GCC countries, with no specific regulations for ordering of other health-related products from local or international OPs.